2023
DOI: 10.1186/s12917-023-03693-2
|View full text |Cite
|
Sign up to set email alerts
|

Pimobendan prevents cardiac dysfunction, mitigates cardiac mitochondrial dysfunction, and preserves myocyte ultrastructure in a rat model of mitral regurgitation

Pakit Boonpala,
Nakkawee Saengklub,
Sirinapa Srikam
et al.

Abstract: Background Pimobendan has been proven to delay the onset of congestive heart failure (CHF) in dogs with mitral regurgitation (MR); however, molecular underlying mechanisms have not been fully elucidated. This study aimed to investigate (1) the effects of pimobendan on cardiac function, cardiac mitochondrial quality and morphology, and cardiac ultrastructure in a rat model of chronic MR and (2) the direct effect of pimobendan on intracellular reactive oxygen species (ROS) production in cardiac c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Moreover, a recent study conducted using a rat model of mitral regurgitation demonstrated the effectiveness of pimobendan in preserving the structural integrity of cardiac mitochondria. The notable increase in mtDNA content observed in groups C and D, in contrast to group B, could reasonably be ascribed to the therapeutic impacts of the medication administered for the management of heart failure [39].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, a recent study conducted using a rat model of mitral regurgitation demonstrated the effectiveness of pimobendan in preserving the structural integrity of cardiac mitochondria. The notable increase in mtDNA content observed in groups C and D, in contrast to group B, could reasonably be ascribed to the therapeutic impacts of the medication administered for the management of heart failure [39].…”
Section: Discussionmentioning
confidence: 89%